PRODUKTIVITAS PENEBANGAN PADA HUTAN JATI (Tectona Grandis) RAKYAT DI KABUPATEN BONE - Andi Mujetahid M. (Forestry Faculty of Universitas Hasanuddin, 2009)
Community teak forest in Bone Regency was +- 4,220 ha in wide, spreading in Amali, Ulaweng, Bengo, Mare, Tonra, Kahu, Salomekko, Ajangale, Dua Boccoe, Lamuru, Tellulimpoe, Lappariaja, Libureng, Palakka, Bontocani and Ponre Subdistricts. The descriptive method was used to describe and clarify felling activities of community teak forest. The quantitative approach was conducted by recording and analyzing the data such as working time, length, diameter, volume, , productivity, etc. Time measurement of each work element with non stop method to get total time. The study was aimed to felling productivity with chainsaw 5,12 m3 /day. Key words: community teak forest, felling, working time, productivity